Prevalence and severity of root caries in qat chewing in Yemen (Thamar) (Mustansiria Dental Journal, 2004)
An epidemiological survey of root caries ni 228 Yemenes individuals aged between 20 years ot more than 60 revealed an age and gender adjusted over all root caries index (RCI) rate of 34% indicating that approximately one ni three surfaces with gum recession exhibited root caries, age adjusted RCI rate were nearly the same figures for both male and female with no significant difference between them, but there was a statistically significant age difference. The study revealed that for severity of the root caries lesion, grade I (incipient) was mostly prevalent for both gender ni the young age groups while, grade II, Ill and VI figures began to increase for both gender in older ages with significant difference, From this study, it my be concluded that root surface caries si a major problem ni people not treated from periodontal diseases, and ni order to provide specific preventive regimes and improved treatment for root surface lesion it is essential that data be collected and the prevalence and distribution of the disease is estimated